Muslim Mistrust: The Resilience of Negative Public Attitudes after Complimentary Information. Issue 1 (2nd January 2016) - Calfano, Brian Robert; Djupe, Paul A.; Cox, Daniel; Jones, Robert
ABSTRACT: Muslims have arguably been the most consistently demonized group in American politics of the past decade, factoring heavily in Republican presidential and congressional politics since 2002. Opinions about Muslims have split the American electorate, and we investigate why. Our explanation focuses on interlocking institutions—party, religion, and media—in encouraging beliefs about American Muslims that prove intransigent. Using data from three nationally representative surveys, including a survey embedded experiment, we examine the correlates of anti-Muslim beliefs. Our analysis finds that ceiling effects in the correlates of holding anti-Muslim attitudes and subject trust in Fox News Channel encourage a negative reaction to information that might repair public opinion about American Muslims.